Reviews of National Policies for Education : Tertiary Education in Chile - Mogollón, Maria Paulina; Crawford, Michael (World Bank, Washington, DC, 2012)
Tertiary education in Chile has been transformed radically over the past 20 years. As recently as 1990, tertiary education was an elite system centered on a handful of traditional universities which served a small number of well-prepared students. Today the system is diverse and dynamic, with over 6,000 programs of study offered by more than 200 institutions. More than 800,000 students are now enrolled, representing over 40 percent of the age cohort. In making this transition, the country has relied on significant development of private tertiary education and the introduction of substantial cost-sharing (tuition and fees) in the entire system. It has coupled this with a strong licensing and quality assurance system, and, increasingly, an innovative and robust student aid system. The aforementioned changes have been a key to Chile's drive for increased competitiveness over the last two decades, and have been consistent with efforts to gain permanent membership in the Organization of Economic Cooperation and Development (OECD). The World Bank assisted the Government of Chile during much of this period, offering both its technical capacity and resources through several loans for human capital development and numerous analytical and knowledge-sharing activities. In 2008, the World Bank and the OECD collaborated to provide a broad assessment of the sub-sector through a comprehensive review of Chile's national policies for tertiary education. The review, tertiary education in Chile, analyzes the achievements of the last decades and outlines the challenges Chile faces in its quest to provide its citizens with a high quality tertiary education system. This note summarizes the main findings and recommendations of the book.